Habituation of Students' Religious Character in Al-Islam and Kemuhammadiyahan Learning at Muhammadiyah 1 Sedati Elementary School: Pembiasaan Karakter Religius Siswa dalam Pembelajaran Al-Islam dan Kemuhammadiyahandi Sekolah Dasar Muhammadiyah 1 Sedati - Wati, Annis; Amrullah, Muhlasin (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze the habituation of students' religious character in ISMU learning at SD Muhammadiyah 1 Sedati. This type of research uses a case study approach. Data was collected through interviews, observations, and documentation by applying triangulation techniques, and sources to teachers and students of class II which was then analyzed using data reduction, data presentation, and drawing conclusions. Based on the results of the study, it showed that the habituation of the religious character of students in Islamic science learning at SD Muhammadiyah 1 Sedati was carried out by habituation of praying before and before doing work, dhuha prayer in congregation which was carried out according to schedule, dhuhur prayer in congregation, reading and writing the Qur'an. before learning begins, tahfidz content, PHBI activities, habituation of religious characters in the content of ismu learning. The conclusion from the conclusion that the habituation of the religious character of students in SD Muhammadiyah 1 is done through habituation taught by the teacher using the tawaqi method, which means the teacher provides an example and theory after the students practice it.